Semantic Analyses of the Text "The Unity of the People of Iveria" 1970 (All the People of Iveria ; the Countries of Highland and Lowland of Iveria ; The Owners of the Same Language ; Affection of Mutual Duties) - Putkaradze, Tariel (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2011)
In the modern international scientific and informational space, language-ethnical history of Georgia is incorrectly represented and it happens quite often. In the last period the claim as if one part of Georgians (mengrels, lazi, svani and meskhi people) doesn’t have Georgian origin became quite casual. Unfortunately the language-ethnical history of Georgians are wrongly represented by some Georgian scientist as well. It’s not accidental that from the 90s of XX century falsification of the scientific positions of historical public men was begun. For example: in 1997 megrels’ dictionary materials created in 1910 by Petre Tcharaia was published; Georgian editor and publisher did a lot of work but, didn’t take into consideration the principles of died author and the work of the great researcher was given the name –Megrels-Georgian dictionary, meanwhile Tcharaia, P believed Megrelian as a dialect of Georgian language. The same kind of “mistake” was made in a dictionary published by Besarion Nijaradze in 2007: Besarion Nijaradze formed bilingual Georgian-Russian dictionary, where the Georgian forms are accompanied by the dictionary materials of svanetian accent. B. Nijaradze considered that the native language of Svani people is Georgian, but publishers didn’t take it into consideration and the dictionary was called trilingual Georgian-svani-Russian dictionary… In this situation giving the objective description of our historical inheritance and spreading Georgians’ language-ethnical existence abroad has great importance. For representing the historical dynamic of Georgians’ language-ethnical situation, the report shows the analyses of several parts from “Treaty of unifying the people of Iveria” The full name of the charter is as followed: “Trwaty, confirmed by the nobles and the kings of Iveria, on the issue of uniting Kartli, Kakheti, Imereti, Odishi and Guria with Tbilisi, the capital city in 1790”. The charter consists of general part at the beginning, and four documents, made by the officials of four Georgian Kigdom, at the beginning we read: “As all the people from Iveria who live in the kingdom of Kartli, Kakheti, Imereti, Odishi and Guria have the same religion, are the sons of one church, and the owners of the same language, they have affection of mutual duties as blood relatives, that’s why the kings and nobles of the both countries of Iveria, promise the strong unity, on behalf of God, and it will be shown in each opinions expressed in the future. (Records of Georgian Justice ii, tb., 1965, pg 501-507). The beginning part is followed by “treaty one”, which is signed by Erekle – king of Kartli, Kakheti, etc, also the Queen of Kartli, Kakheti, etc – Darejan, the Catholicos Anton and vice-chancellor Soloman Lionidze. The replaced three charters of Erekle II belong to king of Imereti – Solomon, the governor of Odishi and other territories Grigol Dadiani, and the governor of Guria-Svimeon. They state about their unification with the people of highland Iveria. The report analyses: All the people of Iveria The countries of highland and lowland The owners of one and the same language The affection of mutual duties Unification